Association between non-invasive nursing care technologies during childbirth and neonatal vitality: a cross-sectional study - Octavio Muniz da Costa Vargens; Carlos Sérgio Corrêa dos Reis; Juliana Amaral Prata; Avany Maura Gonçalves de Oliveira; Jane Márcia Progianti
Abstract Objective: to compare the use of non-invasive midwifery care technologies (TNICEO) with the use of traditional care model practices, having as parameters the presence of meconium in the amniotic fluid and its repercussion on the newborn's vitality. Method: a cross-sectional study with secondary data of 10,219 parturients who delivered by midwives between September 2004 and October 2016. Logistic regression was used to assess Apgar> 8 Odds Ratio in exposure to noninvasive midwifery care technologies when compared to traditional care. Results: there were higher percentages of light amniotic fluid and neonates with good vitality in parturients who used only TNICEO compared with those exposed only to traditional care. Conclusion: nurse midwives' provision of TNICEO and its use by women are efficient strategies to reduce unfavorable neonatal outcomes. Implications of practice: investments in the performance of these experts is important, as their know-how to make them not medicalized through TNICEO confirms a process of humanized, safe and quality care that meets official recommendations and contributes to the change in the care model.